Estudo da matriz vítrea fluoroborotelureto dopada com íons Nd3+ para uso como termômetro óptico próximo ao infravermelho - Melo, Renata dos Santos (2022)
The determination of temperature is a very important physical quantity in several areas of knowledge. In order to monitor the temperature, changes in the physical properties of the sensors are used to obtain thermal information. Optical thermometers are an excellent alternative to conventional thermometers as it offers a quick response and can be a non-contact thermometer. In this work, a study to obtain a near-infrared optical thermometer was realized using a Nd3+-doped fluoroborontellurite matrix, in concentrations of 0.5%, 1.0%, 1.5%, 2.0%, and 3.0%. The study was based on the measured emission intensities of the (4F5/2, 4F3/2) → 4I9/2 transitions in the wide range of temperature from 280 up to 480 K. The changes in the emission band profiles were calibrated by means of the luminescence intensity ratio method, and the results showed that this matrix is a good candidate for an optical thermometer in the near-infrared with a relative sensitivity of 1.58% K−1 at room temperature. The samples with different concentrations of Nd3+ ions were prepared using the melt-quenching technique. The samples were then characterized by DSC, electronic absorption, Raman, emission, and luminescence spectroscopies, and excited state decay measurements.